Case report: Central-pituitary hypothyroidism concurrent with hyperadrenocorticism without pituitary macroadenoma in a Miniature Schnauzer dog - Chae, Yeon; Yun, Taesik; Koo, Yoonhoi; Lee, Dohee; Yang, Mhan-Pyo; Kim, Hakhyun; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2023)
Multiple endocrine disorders are uncommon in veterinary medicine, and the disease combination is usually related to hypercortisolism or autoimmunity. Central-pituitary hypothyroidism, also refer to secondary hypothyroidism, can be caused by hypercortisolemic conditions and is well-recognized in human medicine. However, central hypothyroidism, including pituitary hypothyroidism, concurrent with hyperadrenocorticism, is rarely reported in veterinary medicine. A 7-year-old, intact female Miniature Schnauzer presented with generalized alopecia, scale, and pruritus and was diagnosed with superficial pyoderma and Malassezia dermatitis. Hormonal tests were performed, and the results indicated multiple endocrinopathies with a combination of non-adrenal dependent hyperadrenocorticism and central-pituitary hypothyroidism. Magnetic resonance imaging (7 T) and high-resolution research tomography positron emission tomography were performed to differentiate neuroendocrine tumors; however, no lesion was found in the hypothalamic to pituitary region. Hyperadrenocorticism was managed first to control endocrinopathy. After controlling hypercortisolism, a weak elevation of free thyroxine (T4) was revealed, whereas total T4 and thyroidstimulating hormone (TSH) were still undetectable, and hypothyroidism management was added. About nine months after the management, both endocrine diseases were well controlled, and clinical signs improved; however, serum TSH was unmeasured consistently. This case study describes a case of multiple endocrinopathies in a Miniature Schnauzer dog diagnosed with central-pituitary hypothyroidism concurrent with non-adrenal dependent hyperadrenocorticism without pituitary macroadenoma.